2019
DOI: 10.1088/1757-899x/536/1/012036
|View full text |Cite
|
Sign up to set email alerts
|

Characterization Study of Inorganic Hybrid Membrane of Mixed Activated Zeolite and Clay with PVA Adhesives using Sintering Method for colourless Peat Water

Abstract: The manufacture of inorganic hybrid membranes from the ingredients of activated zeolite (Z), clay (CL), white Portland cement (CW) and PVA adhesive has been carried out on various M1, M2 and M2 material compositions (Z: CL: CW: PVA = 25%: 50%: 20: 5%), (Z: CL: CW: PVA = 50%: 25%: 20: 5%), (Z: CL: CW: PVA = 75%: 0%: 20: 5%) respectively. 100 mesh zeolites are activated using 2M HCL. The membrane is printed in a cylindrical shape with a specification of 69,83x250mm and is burned at a sintering temperature of 500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The permeability or flux of the membrane is affected by the number and size of the membrane pores, the interaction between the membrane and the feed solution, and the operating pressure used. The smaller the pore size, the smaller the resulting membrane flux [14]. In addition, the membrane flux is also influenced by the composition of the membrane material, including the type of polymer chosen, the concentration of the polymer solution used, and the addition of additives used to improve the membrane's mechanical properties [27].…”
Section: Performance Analysis Results Of Cellulose Acetate-zeolite Co...mentioning
confidence: 99%
See 2 more Smart Citations
“…The permeability or flux of the membrane is affected by the number and size of the membrane pores, the interaction between the membrane and the feed solution, and the operating pressure used. The smaller the pore size, the smaller the resulting membrane flux [14]. In addition, the membrane flux is also influenced by the composition of the membrane material, including the type of polymer chosen, the concentration of the polymer solution used, and the addition of additives used to improve the membrane's mechanical properties [27].…”
Section: Performance Analysis Results Of Cellulose Acetate-zeolite Co...mentioning
confidence: 99%
“…The results showed that the membrane was able to reduce turbidity in peat water and improve the membrane's mechanical properties. Thus, it is necessary to modify membranes made from organic polymers by adding inorganic materials [14,15]. Modifying membranes based on organic polymers (cellulose acetate) with the addition of inorganic materials (zeolite) has been carried out and applied in dead-end flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metals, rigid polymers (ceramics), or pyrolysed carbons are common fabrication materials of an inorganic membrane. The purpose of using metals and ceramics in fabricating an inorganic membrane is to add mechanical strength with minimum resistance for mass transfer [86]. Besides, it promotes membrane surface interaction with the desired component, which increases permeation efficiency [40].…”
Section: Inorganic Membranementioning
confidence: 99%